Utilização da pastagem de Cynodon dactylon var.dactylon com diferentes níveis de oferta de lâminas foliares verdes para ovinos - Soriano, Vanessa Souza (2009)
This experiment was conducted with the objective to evaluate a Cynodon dactylon var.dactylon pasture for lambs. It was carried out from January to March of 2008 to test the effect of different green leaf (GLAL) allowances (3, 6 or 9 kg of dry matter (DM)/100 kg of live weight (LW)) on both pasture attributes and animal performance. Thirty six lambs (18 Texel × Ile de France and 18 Lacaune × Texel × Ile de France) were used in a completely randomized experiment that included three pasture plots per treatment. Forage mass was not affected (mean of 3484 kg of DM/ha) whereas the green leaf growth rate (GLGR) increased linearly (P<0.05) from 12.1 to 20.5 kg of DM/ha/day and stocking rate decreased linearly (P<0.05) from 1179 to 609 kg of LW/ha with increased forage allowance. Forage intake (mean of 776 g of DM/animal/day) was not affected by treatments. There was treatment by genetic group interaction (P<0.05) on animal performance such as LW gain was negative (mean of -25 g/animal/day) and not affected by treatments for Texel × Ile de France while it exhibit a quadratic response (P<0.05) with increased forage allowance for Lacaune breed-crossed lambs. Live weight gain of these animals was negative only at the intermediary forage allowance (-61 g/animal/day) whereas it was positive for others treatments (19 and 35 g/animal/day at GLAL of 3 and 9%, respectively). However, more consistent conclusions on nutritional potential of this pasture depend on medium to long-term additional studies carried out in more favorable climatic conditions to both forage and animal growth.